700 W single-frequency all-fiber amplifier at 1064 nm with kHz-level spectral linewidth - Shi, Chaodu; Deng, Xun; Fu, Shijie; Sheng, Quan; Jiang, Peiheng; Shi, Zheng; Li, Yanyan; Shi, Wei; Yao, Jianquan (Frontiers in Physics, 2022)
In this work, a single-frequency fiber amplifier with output power of 703 W was demonstrated at 1064 nm in an all-fiber configuration. Cascaded Yb3+-doped fiber structure with different dopant concentration and hybrid 915/976 nm pump scheme were employed in power scaling stage to improve the gain saturation for higher transverse mode instability threshold. An overall optical efficiency of 67.5% was achieved at the maximum output power and the M2 was measured to be ~1.4. A spectral linewidth of 2 kHz was obtained from the 703-W single-frequency laser. To the best of our knowledge, this is the first time that a single-frequency all-fiber amplifier with kHz-level spectral linewidth is achieved at such high output power.